2020
DOI: 10.1093/pubmed/fdaa049
|View full text |Cite
|
Sign up to set email alerts
|

World leaders’ usage of Twitter in response to the COVID-19 pandemic: a content analysis

Abstract: Background It is crucial that world leaders mount effective public health measures in response to COVID-19. Twitter may represent a powerful tool to help achieve this. Here, we explore the role of Twitter as used by Group of Seven (G7) world leaders in response to COVID-19. Methods This was a qualitative study with content analysis. Inclusion criteria were as follows: viral tweets from G7 world leaders, attracting a minimum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
167
1
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(207 citation statements)
references
References 17 publications
9
167
1
15
Order By: Relevance
“…Twitter, specifically, proved to be a powerful tool for sharing health information. A content analysis of Twitter usage by Group of Seven (G7) world leaders in response to COVID-19 revealed that 82.8% of their COVID-19-related tweets were informative, 9.4% were morale-boosting, and 6.9% were political [30].…”
Section: Response and Implicationsmentioning
confidence: 99%
“…Twitter, specifically, proved to be a powerful tool for sharing health information. A content analysis of Twitter usage by Group of Seven (G7) world leaders in response to COVID-19 revealed that 82.8% of their COVID-19-related tweets were informative, 9.4% were morale-boosting, and 6.9% were political [30].…”
Section: Response and Implicationsmentioning
confidence: 99%
“…An extensive range of tweets has been shared by users and the general public, although politicians (Rufai & Bunce, 2020;Yum, 2020), physicians, and health professionals (Kudchadkar & Carroll, 2020;Wahbeh et al, 2020) have also utilized this platform to share news and provide information to people. Regular users on Twitter share most of their opinions, experiences, and feelings about the crisis.…”
Section: Discussionmentioning
confidence: 99%
“…The use of Twitter during the COVID-19 crisis has many advantages, including immediate communication between people, organizations, and governments, and the rapidity of providing information to people (Abd-Alrazaq et al, 2020;Aguilar-Gallegos et al, 2020;Chen et al, 2020b;Jimenez-Sotomayor et al, 2020;Kudchadkar & Carroll, 2020;Mackey et al, 2020;Thelwall & Levitt, 2020). Moreover, the data available on Twitter is used as a source for identifying geographical areas at risk and the outbreak of COVID-19 (Bisanzio et al, 2020;Klein et al, 2020;Mackey et al, 2020;Rufai & Bunce, 2020). Therefore, this data is increasingly useful for enhancing situational awareness and assisting in disaster management (Wang et al, 2015;Yang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As of April 20, 2020, already seven (7) papers on the topic of tracking and forecasting COVID-19 using Google Trends data have been published, according to PubMed (advanced search: covid AND google trends) [22], monitoring, analyzing, or forecasting COVID-19 in several regions like Taiwan [23], China [24][25], Europe [26][27], USA [27][28], Iran [27,29]. Note that for Twitter publications related to the COVID-19 pandemic, eight papers (8) are online up to this point (PubMed advanced search: covid AND twitter [22]), published from March 13 to April 20, 2020 [30][31][32][33][34][35][36][37]. Table 1 consists of the systematic reporting of COVID-19 Google Trends studies, in the order of the reported publication date.…”
Section: Cases Deathsmentioning
confidence: 99%